Can Chronic Remote Cortical Hypoperfusion Induced by Thalamic Infarction Cause Damage of Tracts Passing through Those Hypoperfused Regions? - Magnin, Eloi; Chamard, Ludivine; Vuiller, Fabrice; Tatu, Laurent; Berger, Eric (Frontiers in Neurology, 2013)
We report the case of a woman presenting with changes on cerebral imaging a year and a half after a bi-thalamic (predominantly left-sided) infarction including lateral and medial thalamic nuclei. Lateral geniculate body and pulvinar were not damaged. Hypoperfusion was observed in left cortical and basal structures. White matter FLAIR hyperintense lesions occurred in the left hemisphere and the occipital region one year and half after stroke. Medial and lateral thalamic nuclei are not highly connected to the occipital cortex. Therefore, in addition to Wallerian degeneration after thalamic stroke, we hypothesize that the chronic left temporal hypoperfusion induced by diaschisis can lead to a lateralized chronic hypoxic damage of the occipital fiber tract (optic radiation) that passes through the temporal lobe.